The Role of Prostaglandin-Endoperoxide Synthase-2 in Chemoresistance of Non-Small Cell Lung Cancer - Lin, Xiao-mian; Luo, Wu; Wang, Heng; Li, Rong-zhen; Huang, Yi-shan; Chen, Lian-kuai; Wu, Xiao-ping (Frontiers in Pharmacology, 2019)
The prostaglandin endoperoxide synthase-2 (PTGS2) plays essential roles in diverse pathological process. Although recent studies implied PTGS2 was closely related with chemoresistance, the precise roles and the underlying mechanisms of PTGS2 in the developing process of chemoresistance in non-small cell lung cancer (NSCLC) remained elusive. In the present study, we revealed a novel molecular mechanism of PTGS2 implicated in the chemoresistance of NSCLC, and proposed a model for the positive feedback regulation of PTGS2 in the process of developing resistance phenotype in NSCLC cells. Our results demonstrated that cisplatin induced PTGS2 expression through ROS-ERK1/2-NF-κB signaling axis. The prostaglandin E2 (PGE2) derived from PTGS2 catalyzation further strengthened PTGS2 expression via PGE2-EPs-ERK1/2 positive feedback loop, which induced multidrug resistance of NSCLC cells through up-regulation of BCL2 expression and the subsequent attenuation of cell apoptosis. Consistently, high levels of both PTGS2 and BCL2 were closely associated with poor survival in NSCLC patients. Inhibition of PTGS2 significantly reversed the chemoresistance in the resistant NSCLC in vitro and in vivo. Our results suggested that PTGS2 might be employed as an adjunctive therapeutic target for improving the response to the therapeutic agents in a subset of resistant NSCLC.